PARTISIPASI MASYARAKAT DALAM COMMUNITY BASED TOURISM DI DESA WISATA PUTON WATU NGELAK KABUPATEN BANTUL - Mesalia Kriska; Riesma Andiani; Theresia Grace Yunindi Simbolon (University of Jember, 2019)
Puton Watu Ngelak Tourism Village is one of the tourist villages that implements Community Based Tourism, so that it requires community participation in its management. This Tourism Village presents the beauty of natural resources in the form of Opak River and Watu Ngelak site, combined with art and cultural performances that are requires an educational content. The contribution of local communities in the formation and development of Puton Watu Ngelak Tourism Village is interesting to study in relation to the realization of community empowerment in rural areas. The research method used is descriptive analytical. This research was conducted in Puton Hamlet with research informants, namely residents of Puton Hamlet This research uses primary and secondary data and the data are collected through observation and interview. Data analysis will be conducted descriptively by presenting the percentage of community involvement in the management of Puton Watu Ngelak Tourism Village. The results showed that community performed high participation of labour and idea. On the other hand, their participation in providing materials is still low/minimum because they prioritize their family needs rather than the tourism village development.